Service value exchange in B2B electronic marketplaces. Issue 6 (6th July 2015) - Standing, Susan; Standing, Craig
Abstract : Purpose: – This paper aims to explore what aspects of organisational value can be realised through taking a service exchange perspective of e-marketplaces as opposed to a product transaction perspective Marketing is increasingly concerned with the notion of service value in business-to-business markets. Electronic marketplaces (e-marketplaces) have been used in B2B exchanges for many years and continually evolve as the understanding of e-marketplace participation and the technologies develop. Design/methodology/approach: – A case study approach is taken using three large e-marketplace organisations and interviews with senior managers from each company. Findings: – The paper argues that e-marketplaces should not be thought of solely as a product transaction mechanism but rather as a digital marketing and communication network where service, rather than products, forms the basis of a value creating exchange. Practical implications: – Organisations can co-create value within an e-marketplace network but must market services value across organisational boundaries. Originality/value: – The paper extends the literature in the area of e-marketplace trading and recognises the importance of the digital communication network in enabling service exchange between the e-marketplace, buyers and suppliers.